From the Editor: Welcome to Day 196. (December 2020) - Kelly, Rob
Abstract : I think I speak for everyone when I say that I have serious virus fatigue. Everybody is getting a bit grumpy at times. (Of course, no one in my house.) The times in which we are living seem to be conspiring to tax everyone's patience and better angels. At least here in the U.S., some appear to interpret the wearing of a mask as an in-your-face political statement as opposed to an on-your-face public health action.